THE EFFECT OF GUIDED INQUIRY LEARNING MODEL ON STUDENTS’ LEARNING OUTCOMES ON ADDITIVE AND ADDICTIVE TOPIC - Andriziaswari, Ghina Reysa; Lestari, Tuti; Azhar, Aulia; Yanto, Febri (SEMESTA: Journal of Science Education and Teaching, 2024)
The research is to find out how guided inquiry affects student learning outcomes. The type of research used is quasi-experimental. Research design non equivalent control group design The population of this study consisted of class VIII students at SMPN 26 Padang TP 2023/2024. In the research sample, class VIII.8 was the experimental group and class VIII.4 was the control group. The guided inquiry education model has been implemented with a high level of success, with an average success rate of 95%. Students are enthusiastic about the guided inquiry learning model, 53% strongly agree and 47% agree in the SMPN 26 Padang questionnaire which shows how the guided inquiry learning influences student learning outcomes